Strategi Perlindungan Tenaga Kerja di Era Kecerdasan Artifisial: Studi Kasus pada Sektor Industri Manufaktur - Kuswoyo, Muhammad Riko; Purwasih, Ratih; Sendi Pria Ardana; Rizky Putra Fhonna; Hasibuan, Arnawan (Multiverse: Open Multidisciplinary Journal, 2025)
The rapid development of Artificial Intelligence (AI) has profoundly reshaped the manufacturing sector, boosting productivity while intensifying concerns over job displacement. This study investigates strategic measures to safeguard the workforce amidst increasing AI integration, using Indonesia’s manufacturing industry as a case study. Employing a qualitative research design, the study adopts a case study approach supported by in-depth interviews with key stakeholders and comprehensive policy analysis. The results indicate that effective workforce protection demands a multifaceted strategy encompassing reskilling initiatives, regulatory frameworks specific to AI, and cross-sector collaboration among government, industry, and academia. The study recommends enhancing digital skills training, offering incentives for industries that implement inclusive labor transitions, and establishing equitable AI governance. In conclusion, the research highlights critical pathways for fostering a balanced coexistence between technological innovation and labor security in the era of automation.